Ekonomi Politik Media dalam Perspektif Komunikasi dan Sosial-Budaya - Imsar; Husaini, Ahmad (As-Syirkah: Islamic Economic & Financial Journal, 2023)
Harold Innis and Marshall McLuhan recognized the fact that technologies have a communicative dimension in and of themselves and play an important role in the formation of political economy. The economic field clearly cannot be separated from capitalism; and capitalism and industry are two things that cannot be tolerated. Furthermore, culture is one of the most interesting contents to be "sold" and is often massified by the media to generate huge profits by media capitalists. This study aims to discuss how the political economy of media is viewed from a communication and socio-cultural perspective. The study in this article uses a descriptive-qualitative method, using literature review as a data collection technique. The results show that the political economy of (mass) media is closely related to power and control over mass media content. This control is carried out through a communication process, where the messages conveyed by the mass media aim to influence the audience's perception, sometimes also to guide the audience's attitude towards an issue, especially social and political issues. One content medium that is considered effective for gaining financial resources is culture. Massified culture becomes a powerful weapon for media owners to gain profits and wealth; where culture is no longer viewed from an aesthetic perspective alone, or how culture conveys truth, but is seen as a "tool" to gain profit alone.